2012
DOI: 10.1016/j.ajog.2012.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory stimulation by microparticles derived from hypoxic trophoblast as a model for inflammatory response in preeclampsia

Abstract: OBJECTIVE To determine whether trophoblast-derived microparticles can induce different inflammatory responses of the peripheral blood mononuclear cells (PBMCs) depending upon the state of trophoblast when the microparticles are generated. STUDY DESIGN A trophoblast-derived cell line (ATCC No. CRL-1584) was cultured under normal or hypoxic conditions. Microparticles were isolated from the cell culture supernatants (MP_C: microparticles from normal trophoblast; MP_H: microparticles from hypoxic trophoblast). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 43 publications
0
51
1
1
Order By: Relevance
“…Placental hypoxia, which is the main pathologic feature of PE, can cause trophoblast hypoxia, necrosis, and apoptosis (8,9). HMGB1 released actively or passively by hypoxia trophoblast increased the permeability of endothelial cell monolayer by TLR4-CAV-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Placental hypoxia, which is the main pathologic feature of PE, can cause trophoblast hypoxia, necrosis, and apoptosis (8,9). HMGB1 released actively or passively by hypoxia trophoblast increased the permeability of endothelial cell monolayer by TLR4-CAV-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that HMGB1 increases endothelial cell permeability in sepsis and cerebral ischemic pathogenesis by activation of pattern recognition receptors, TLR4, TLR2, and the receptor for advanced glycation endproducts (RAGE) (11,12). High endothelial cell permeability is the main cause of general edema and high urine protein in PE (8); however, the underlying pathogenic relationship between HMGB1 and endothelial cell dysfunction in PE remains unexplored.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…73 In addition, in vitro research has indicated that PE-derived STBEVs differentially affect immune cells, endothelial cells, and platelet activation, suggesting a key role in maintenance of the MSIR. 74 STBEVs have been identified in maternal circulation in the first trimester of normal pregnancy and also found to be significantly elevated in early-onset PE. 75 Moreover, it is known that STBEVs contain subpopulations of EVs.…”
Section: Syncytiotrophoblast Extracellular Vesiclesmentioning
confidence: 99%